Optimalisasi Rumah Pintar sebagai Pemberdayaan Perpustakaan Desa Urek-Urek, Kecamatan Gondanglegi - Mudhofar (Lembaga Penerbitan dan Publikasi Ilmiah, 2024)
Rumah Pintar is part of a means of community empowerment to build a culture of reading literacy among the community. This village library is a community pioneer that is aware of the importance of non-formal education and literacy. In this community empowerment program, Rumah Pintar is the partner that is the target of the work program. The aim is to strive to optimize the functions, goals and benefits of the existence of the Rumah Pintar itself. This community empowerment program through revitalization and optimization of village libraries aims to sharpen people's interest in reading again.